A política fiscal brasileira no período de 1995 a 2010, com ênfase no comportamento da despesa governamental - Amaral, Leandro Gomes (2012)
This study aims to analyze the Brazilian fiscal policy in the period 1995 to 2010, especially government spending, so that one can opine about the character procyclical or countercyclical that. We can say that the measures adopted by the Brazilian government were pro-cyclical during almost every year belonging to the period 1995-2010, except 2001 and 2009. In these years, fiscal policy was countercyclical, given the tax cuts in 2009 and the increase of fixed capital formation of government in both. However, it wasn t identified evidence that the expansion of investment occurred in 2001 was deliberate, unlike 2009, when the Federal Government aimed to mitigate the recessionary phase of the cycle, as proposed by Keynes. Therefore, the fiscal stimuli to aggregate demand were possible because the economy was in a position to absorb during crisis possible adverse effects of tax cuts, the increase in public investment and reducing the primary surplus